Interactions between Arctic and Red Foxes in Scandinavia - Predation and Aggression - Frafjord, Karl; Becker, Dennis; Angerbjörn, Anders (ARCTIC, 1989)
Arctic fox (Alopex lagopus) populations in Scandinavia are small and restricted to alpine regions, while red foxes (Vulpes vulpes) are common throughout both Norway and Sweden. The two species are similar in behaviour and diet, and thus competition between them is likely. This study provides seven observations of aggressive interactions between the two species. One adult arctic fox and one cub were killed by red foxes, one male arctic fox was chased away from his den, one female arctic fox and a cub fled into the den as a red fox approached, four cubs fled into the den as a red fox walked upon it and once a red fox walked upon the arctic fox den when no arctic foxes could be seen. Only on one occasion did an arctic fox succeed in chasing away a red fox. Red fox predation may prove to be limiting to the small arctic fox population in Scandinavia, and arctic foxes can be displaced from good dens and the most productive regions.Key words: arctic fox (Alopex lagopus), red fox (Vulpes vulpes), interactions, predation, aggression, field observations, Scandinavia Mots clés: renard polaire( Alopex lagopus), renard roux (Vulpes vulpes), interactions, prédation, agression, observations sur le terrain, Scandinavie